Evaluación de inmunoglobulinas g pre y post parto, en corderos (4m) en el núcleo genético yanahurco del cantón Saquisilí provincia de Cotopaxi. - Sandoval Palacios, Sídney Karolina (2020)
Immunoglobulins G, is a major factor in the development of newborn lambs. As for colostrum, it plays an important nutritional role, being the only source of energy at this age, but it is fundamental in the transfer of passive immunity, due to the tissue characteristics of the placenta, not enough immunoglobulins G are transmitted from the mother to the fetus. Thus, we studied the genetic nucleus of Yanahurco of the 4M race in Saquisilí canton, Cotopaxi Province, where we analyzed through chemiluminescence the pre-birth, post-birth and lamb immunoglobulins G. Six animals of the same age were chosen, which were divided between single and double pregnancy, about 5 ml of blood was extracted from each animal, which were identified in a yellow gel tube, transported in a cooler to the laboratory for analysis, this was the first antepartum sampling, after approximately one month the following sample of postpartum animals was made with the same procedure, in their offspring was made within the first days of life. As a result of our first antepartum study, we obtained an average of 542.6 ± 42.15 EE in single birth and 491.47 ±81.39EE in double birth with p= 0.6067, observing homogeneity in single birth. As for single postpartum 750.37±75.47 EE in double postpartum 695.1±68.30 EE p=0.616 where single delivery increased its production of immunoglobulins G. In lambs, single birth twins were analyzed separately, where twins were compared as calf 1 and calf 2, which obtained a mean of 640.13±59.88 EE and 626.83±42.41EE respectively, p =0.865 and in single birth calves a mean of 435.37 with a p =0.0086.